Zelada family (Journal of Parents and Teachers, 2025)
Family life is essential for the growth of children, but also for parents. As an example, we have the Zelada family, made up of the parents (Cristina and Jorge) and four children (Juan, Jorge, Jacobo, and José). This article presents a very interesting interview, based on an open, sincere, and simple dialogue. The experiences they have shared while living in different countries have brought them closer together, allowing them to strongly experience each other's support, grow in their sense of humour and also discover and develop a talent that accompanies them: music. The Zeladas gradually became interested in music and formed a band that started out playing well-known songs, but soon began to perform their own compositions. This family understands that living together, which also involves conflicts, is key to growing and facing situations that lie beyond the family reality.
Keywords: family, coexistence, conflict, learning, music